FOREST protocol: a qualitative study exploring health and sexuality of transmasculine individuals in France - Marion Mora; Dulce Ferraz; Xavier Mabire; Marie Préau; Suzanne Robin-Radier; Alexandre Baril; Emmanuel Beaubatie; María Del Río Carral; Céline Dentella; Véronique Ginouvès; Lucie Pallesi; Clark Pignedoli; et al. (BMJ Open, 2021)
Introduction While current research on sexuality and health often explores sexual behaviours among heterosexual and gay cisgender individuals, little is known about the sexualities of transgender people, especially transmasculine people. When data are available, sexual health is often reduced to risk exposure, not considering in detail social context and determinants that could contribute to a more comprehensive approach, such as general health, class, race, exposure to violence or social representations. Recognising this gap, identified in both national (French) and international scientific literature, this study aims to explore the sexual health of transmasculine people, employing an intersectional approach and considering both positive and negative health determinants.Methods This 2-year research based in the disciplinary field of social psychology, with a gender perspective, and will apply qualitative methods. We adopt a community-based research approach, integrating one university and one community-based organisation in the coordination of the study. In a triangulation perspective, two rounds of semistructured interviews will be performed with key informants (medical practitioners, community-based support services workers, etc) and with people self-identifying as transmasculine. Focus groups will complement data collection.Ethics and dissemination FOREST protocol was approved by the Comité d’Évaluation Éthique (CEEI) de l’Institut National de la Santé Et de la Recherche Médicale (CEEI/International Review Board 00003888). The research adopts the principles of open science, and findings will be published assuring participants’ confidentiality. Informative flyers and videos will be elaborated to communicate study findings to participants, stakeholders and the transcommunities at large, and data will be stored in lasting archives.